ADVANCED EXPERIENCE OF DEVELOPED FOREIGN COUNTRIES IN THE EFFECTIVE USE OF UNMANNED AERIAL VEHICLES IN NATIONAL GUARD UNITS TO ELIMINATE MASS RIOTS AND PROSPECTS FOR THEIR USE IN OUR COUNTRY (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
in recent years, many countries have begun to deploy unmanned aerial vehicles (UAVs) - drones - in crowd‑control operations. This article examines the current use of UAVs by the National Guard of Uzbekistan to manage disturbances, reviews the experiences of France, Turkey, the United States, Israel, Spain and other states, and outlines prospects for future deployment. The authors discuss five main functions of drones in public‑order missions: psychological influence (loudspeakers, banners and colour signals), leaflet distribution, surveillance and intelligence, delivery of urgent medical supplies and transport of necessary weapons and ammunition. Based on official statistics from 2021-2025, a simple regression model evaluates the effectiveness of UAV deployment and its impact on crime trends.